2014
DOI: 10.1097/mbc.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed chronic thromboembolic pulmonary hypertension after pulmonary embolism

Abstract: Chronic thromboembolic pulmonary hypertension is associated with adverse prognosis. Early diagnosis is important to better identify patients who would benefit from a well established therapeutic strategy. The purpose of our study was to evaluate long-term incidence of undiagnosed chronic thromboembolic pulmonary hypertension after acute pulmonary embolism and the utility of a long-term follow-up including an echocardiographic-based screening programme to early detect this disease. We evaluated retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…10 Subsequent studies have reported a prevalence ranging between 0.4% and 4.8%. [11][12][13][14][15][16][17] Differences in rates are likely due to differences in populations studied, screening methods for CTEPH, and length of follow-up.…”
Section: Epidemiologymentioning
confidence: 99%
“…10 Subsequent studies have reported a prevalence ranging between 0.4% and 4.8%. [11][12][13][14][15][16][17] Differences in rates are likely due to differences in populations studied, screening methods for CTEPH, and length of follow-up.…”
Section: Epidemiologymentioning
confidence: 99%
“…The diagnosis should be made as soon as possible to prevent progression of RV overload and dysfunction and to improve prognosis and the patient’s quality of life. Most importantly, the possibility of CTEPH must be taken into diagnostic consideration because it is an often under-diagnosed disease (21). Every tool helping us to reveal CTEPH in the early disease stages is welcome because we are still not able to identify patients who develop CTEPH after PE for effective follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent estimates of CTEPH incidence have varied according to study population, with range 0.6-4.6% when diagnosis requires catheterization [2][3][4][5][6]. The risk of developing CTEPH after acute pulmonary embolism is greater in those with recurrent pulmonary…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%